Detection and dynamics of anti‐platelet antibodies in thrombocytopenic dogs with and without idiopathic immune thrombocytopenia. (18th February 2020) - Shropshire, Sarah; Dow, Steven; Lappin, Michael
Abstract: Background: Antiplatelet antibodies are detected in multiple diseases including primary immune thrombocytopenia (ITP). Dynamics of how these antibodies change over time in ITP is unknown in dogs. Hypothesis/Objectives: Antiplatelet antibodies (APA) will be detected in thrombocytopenic dogs with multiple etiologies and dynamics of APA in dogs with ITP can be used to evaluate response to treatment and relapse. Determine APA at the time of diagnosis in thrombocytopenic dogs and serially in primary ITP dogs. Animals: Seventy‐nine thrombocytopenic dogs and 28 primary ITP dogs. Methods: Direct flow cytometry was performed in thrombocytopenic dogs at initial evaluation and serially in suspected primary ITP dogs. In primary ITP dogs, a 2‐tailed Fisher's exact test was performed comparing survival to discharge between dogs with and without melena and to relate response to treatment and relapse to changes in APA and platelet count (repeated measures analysis, Spearman correlation). Results: Twenty percent (16/79) of thrombocytopenic non‐ITP dogs with infectious, neoplastic, or other diseases and all primary ITP dogs were positive for APA. Melena at initial evaluation was associated with decreased survival to discharge (odds ratio 0.06; P = .01). Persistence of APA was not associated with response to treatment, but recurrence of antibodies was associated with relapse (odds ratio 205.0; P < .01). There was no difference in percentage of APA or platelet count at initial diagnosis between dogs that did or did not respond to treatment. Conclusions and Clinical Importance: Serial monitoring of APA in dogs with primary ITP appeared beneficial for determining relapse of disease.